APPLICATION OF QUINOA FLOUR IN WHEAT BREAD TECHNOLOGY - Bolgova, N. V.; SoloveiV. І. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2023)
The article considers the perspective of using high-protein plant additives in the bakery industry using the example of kino flour. The analysis of the study of this issue allows us to state that kino is an extremely promising high-protein additive, however, the percentage of its application and the technology of preparation before application should be selected, which will allow to preserve the biological value and ensure optimal organoleptic properties of the finished product. The method of research is the substantiation of the recipe of wheat bread with the addition of regional kino of the Quartet variety. The object of the study is the technology of wheat bread production by steam method. It is proposed to add quinoa flour to the recipe of bakery products by replacing part of the wheat flour with quinoa flour. Recipes of 3 samples were developed with the replacement of 5, 10 and 15% of wheat flour with quinoa flour. For the preparation of bread, quinoa seeds of the Quartet variety were used, adapted to our climatic conditions, which were selected and grown at the Sumy National University. Research and analysis of the organoleptic and physicochemical indicators of the products has been carried out. According to the results of the organoleptic evaluation, it can be concluded that the optimal amount of replacing wheat flour with quinoa flour is 10%. The resulting product not only meets the requirements of regulatory documentation, but also acquires new taste and aroma characteristics characteristic of the introduced additive. It should be noted that the replacement of wheat flour with quinoa flour had a positive effect on the porosity of the bread, increasing the indicator by 6%. Therefore, according to the physical and chemical indicators, the second sample did not exceed the permissible standards and was better than the control. Conclusions. It was established that the addition of high-protein additives to the dough instead of part of the wheat flour contributes to the intensification of the fermentation process and changes in the structural and mechanical properties of the dough: an increase in water absorption capacity, the speed of dough formation, and a decrease in its fuzziness. The optimal amount of flour replacement is 10%. It was determined that the introduction of such a quantity of quinoa flour into the recipe contributes to the improvement of organoleptic and physicochemical indicators. The feasibility of using quinoa flour in the bakery industry to increase the share of new products is substantiated.